SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN UKM/HMJ PENERIMA BANTUAN DANA TAKTIS DENGAN METODE ELECTRE DAN WEIGHTED PRODUCT - Ivan Novandy S; Anggraini Kusumaningrum (Institut Teknologi Dirgantara Adisutjipto, 2015)
Student Executive Board (SEB) is a campus organization which is an executive agency at the level of the University / Institute / College. Constraints experienced by the SEB in determining UKM / HMJ tactical beneficiaries. To be able to assist in making decisions to determine UKM / HMJ beneficiaries needed a tactical decision support system (DSS). The system can use the ELECTRE method and Weighted Product method in the calculation process. The results showed that the proposal with the highest values approaching the highest value of 1 (one) is the proposal of UKM/ HMJ are eligible to receive financial assistance tactical.